2021
DOI: 10.1002/jcla.23808
|View full text |Cite
|
Sign up to set email alerts
|

White blood cells and platelet profiles of diabetic patients at University of Gondar specialized referral hospital: A comparative cross‐sectional study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
(35 reference statements)
5
13
0
Order By: Relevance
“…On the other hand, the mean of Hct, MCV, MCH, and RDW-SD was statistically significantly low in T2DM patients as compared to the healthy control group. This result was similar to the findings reported in India, Brazil, Saudi Arabia, Sudan, and Ethiopia in which MCH, MCHC, hematocrit, and RDW-SD were significantly reduced in diabetes compared to healthy controls [ 9 , 27 30 ]. In diabetic patients, multiple risk factors such as hyperglycemia, hyperosmolarity, oxidative stress, inflammation, and lipid metabolic disorder may affect RBCs metabolism as they may increase aggregation, reduce cell deformability, and reduce membrane fluidity.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the mean of Hct, MCV, MCH, and RDW-SD was statistically significantly low in T2DM patients as compared to the healthy control group. This result was similar to the findings reported in India, Brazil, Saudi Arabia, Sudan, and Ethiopia in which MCH, MCHC, hematocrit, and RDW-SD were significantly reduced in diabetes compared to healthy controls [ 9 , 27 30 ]. In diabetic patients, multiple risk factors such as hyperglycemia, hyperosmolarity, oxidative stress, inflammation, and lipid metabolic disorder may affect RBCs metabolism as they may increase aggregation, reduce cell deformability, and reduce membrane fluidity.…”
Section: Discussionsupporting
confidence: 91%
“…Although the percentage of patients with leukocytosis is not stated, previous research has shown that leukocytosis is a common symptom in patients with T1DM. Findings from studies conducted in Ethiopia, 36 Nigeria, 37 and Bangladesh 38 confirm that the mean value of total WBC count was higher in patients with DM than in non-diabetic controls. The increase in WBC count mainly reflects the elevated neutrophil and lymphocyte count in these studies.…”
Section: Discussionmentioning
confidence: 90%
“…This is similar to a study done in Ethiopia which report that platelet counts were significantly higher in patients with DM than in the controls. 36 Besides, studies have shown that there is no significant difference in the mean platelet count between children with T1DM and healthy controls. 25 , 35 Possible mechanisms for the increased platelet count in DM are related to hyperglycemia, insulin deficiency and resistance, and associated metabolic cellular abnormalities and therefore increase the risk of thrombotic and vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a group of metabolic disorders characterized by abnormal carbohydrate metabolism resulting in chronic hyperglycemia caused by defective insulin production [1]. Several studies have shown that T2DM predisposes to a multifactorial prothrombotic state, in which endothelial dysfunction, platelet hyper-reactivity, alterations of the coagulation cascade, impaired fibrinolysis, as well as chronic low-grade inflammation, are known to play a major role [2].…”
Section: Introductionmentioning
confidence: 99%